Cultural and Identity Values of the Rugova Region in Function to Develop Tourism in Kosovo - LAJÇI, Dardan; KUQI, Bekë; KARJAGDIU, Lirak (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
Natural and socio-cultural heritage for the tourism development of a country or different countries of the world is a prerequisite for sustainable development. Monuments of nature and culture are part of the identity of a nation and important factors of its economic and social development. Monuments of nature and culture, handicrafts, cooking, etc., can be opportunities as an object of construction of tourist projects. Rugova region is known for a series of rich characteristics such as: Wild trees, forests, lakes, rich fauna and flora, mountain tourism, water resources, cultural values, especially in the category of Epic, folklore, toponyms, traditional Rugova man's clothing, woman and girl, white scarf as a special feature of the elderly inhabitants of the area, etc., which indicate a place that still produces traditional values. There is also a tradition of food, a tradition of towers, special architectural construction that enables the development and use of natural resources. The production and processing of medicinal plants also enables a contribution to mountain tourism. The research method was used to use all existing literature on cultural heritage and tourism development in the mountainous region of Rugova. Various studies and publications of local and foreign archaeologists, sociologists and scholars on cultural heritage and mountain tourism have been used.